2020
DOI: 10.1093/molehr/gaaa074
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2-induced epithelial–mesenchymal transition is reversed by let-7d in intrauterine adhesions

Abstract: Intrauterine adhesions (IUA), the leading cause of uterine infertility, are characterized by endometrial fibrosis. The management of IUA is challenging because the pathogenesis of the disease largely unknown. In this study, we demonstrate that the mRNA and protein levels of HMGA2 were increased by nearly 3-fold (P < 0.0001) and 5-fold (P=0.0095) in the endometrial epithelial cells (EECs) of IUA patients (n = 18) compared to controls. In vivo and in vitro models of endometrial fibrosis also confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, numerous studies have indicated that transforming growth factor (TGF)-β is a cytokine that participates in regulating diverse biological functions, including cell proliferation, apoptosis, and differentiation [ 11 , 12 ]. Importantly, previous studies have reported that TGF-β can induce endometrial fibrosis [ 13 , 14 ] and TGF-β treated ESC can serve as the in vitro model of IUA [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies have indicated that transforming growth factor (TGF)-β is a cytokine that participates in regulating diverse biological functions, including cell proliferation, apoptosis, and differentiation [ 11 , 12 ]. Importantly, previous studies have reported that TGF-β can induce endometrial fibrosis [ 13 , 14 ] and TGF-β treated ESC can serve as the in vitro model of IUA [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of IUA increases each year, effective treatment options to reduce the incidence of re-adhesion and promote fertility remain lacking [9]. Potentially, activated fibroblasts may be derived from resting fibroblasts in the tissue, via epithelial-to-mesenchymal transformation, or from the bone marrow [25], [35,36]. In this study, we demonstrate for the first time that endothelial cells also promote the emergence of Further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 70%
“…High mobility group AT-hook 2 (HMGA2) was regarded as an important regulator in EMT processes in some fibrotic diseases, such as pulmonary fibrosis, lens fibrosis and renal fibrosis. Similarly, in IUA patients and animal models, Song et al ( 21 ) also observed the overexpression of HMGA2 directly mediated EMT. They further found that HMGA2 expression can be directly inhabited by let-7d to protect EEC from EMT.…”
Section: The Formation Of Iuamentioning
confidence: 83%